Understanding how children view the world: advancements, barriers, and future directions - Woodard, Shailee R. (Frontiers in Developmental Psychology, 2025)
This paper outlines recent advances and proposes future directions in the study of child worldviews. Over the past decade, the field of developmental psychology has made significant strides in understanding how children form and revise their beliefs, as well as how these beliefs relate to their behavior and mental health. Despite these advancements, the field continues to lack extensive research on whether and how children's individual beliefs are organized into cohesive worldviews. Findings from adult research on worldview composition and structure are used to highlight these gaps in the developmental literature and to generate hypotheses concerning the nature of children's worldviews. Specifically, it is hypothesized that (1) children will have beliefs on many of the same worldview dimensions as adults (though children's worldview beliefs are likely to be more concrete and specific than adults'), (2) these beliefs form through children's direct experience and social learning processes, (3) worldview beliefs inform children's behaviors, and (4) these beliefs are resistant to change. Future research is necessary to test these hypotheses; however, numerous methodological challenges hinder such studies. Recommendations are offered to address these challenges, including the development of new instruments for assessing beliefs.